Psycho-Social Behaviour and Employee Absenteeism: An Evidence from Nepalese Commercial Banks (Saptagandaki Journal, 2025)
This study examines the key behavior of employee absenteeism in Nepalese commercial banks by integrating organizational, psychological, and socio-cultural factors. It seeks to identify the most influential predictors affecting employee attendance and provide actionable recommendations to improve organizational performance and productivity. A quantitative research design was employed using primary data from 420 employees across 20 commercial banks in Nepal. Data were obtained through a structured questionnaire using a 5-point Likert scale. Descriptive statistics, correlation, and multiple regression analyses were applied to examine the relationship between employee absenteeism and its determinants. Reliability was confirmed using Cronbach’s alpha. The study found that job stress, workplace policies, socio-cultural obligations, job satisfaction, work environment, and organizational support significantly influence absenteeism. Sociocultural obligations and job satisfaction emerged as the strongest predictors, while commuting distance showed no significant effect. The results support the Job Demands–Resources (JD-R) model and the Process Model of Absenteeism. The practical implication of the study is that banks can reduce absenteeism by introducing stress management programs, flexible workplace policies, and improved organizational support to enhance job satisfaction and employee well-being. Similarly, reducing absenteeism improves service quality, strengthens employee well-being, and contributes to social stability and economic productivity in Nepal’s financial sector.Thus, this study provides one of the first integrated analyses of organizational, psychological, and socio-cultural determinants of absenteeism in Nepalese commercial banks, offering a holistic understanding and practical insights for managers and policymakers.